2015
DOI: 10.1134/s0006297915060061
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence assay for cell viability

Abstract: Theoretical aspects of the adenosine triphosphate bioluminescence assay based on the use of the firefly luciferin-luciferase system are considered, as well as its application for assessing cell viability in microbiology, sanitation, medicine, and ecology. Various approaches for the analysis of individual or mixed cultures of microorganisms are presented, and capabilities of the method for investigation of biological processes in live cells including necrosis, apoptosis, as well as for investigation of the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 62 publications
0
53
0
Order By: Relevance
“…ATP decrement is usually linked to a cytotoxic effect; nevertheless, Wickersham et al observed that metabolic stressed keratinocytes were more active in the response to bacterial infections. This finding is particularly attractive for our research, in fact, HaCaT knockout for NCSTN after irradiation could be more prone in fighting against infections, an issue that in HS lesions occurs. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP decrement is usually linked to a cytotoxic effect; nevertheless, Wickersham et al observed that metabolic stressed keratinocytes were more active in the response to bacterial infections. This finding is particularly attractive for our research, in fact, HaCaT knockout for NCSTN after irradiation could be more prone in fighting against infections, an issue that in HS lesions occurs. …”
Section: Resultsmentioning
confidence: 99%
“…[36] ATP decrement is usually linked to a cytotoxic effect; nevertheless, Wickersham et al observed that metabolic stressed keratinocytes were more active in the response to bacterial infections. [37,38] This finding is particularly attractive for our research, in fact, HaCaT knockout for NCSTN after irradiation could be more prone in fighting against infections, an issue that in HS lesions occurs. [39,40] 3.2 | PBM stimulated wound closure and keratinocytes migration without affecting proliferation or influencing cell cycle progression Skin keratinocytes are key cellular component of the epidermis that, after injuries such as wounds, are essential during the process of reepithelialization.…”
Section: Pbm-induced Metabolic Activation Of Hacat Cellsmentioning
confidence: 99%
“…The ATP concentration can be quickly and easily determined using bioluminescence with great accuracy, even with an ultralow content of the substance in the sample (as low as 10 −14 ÷ 10 −12 M), using luciferin-luciferase reagents [16,17]. Portable luminometers make measuring the ATP concentration possible both in the laboratory and in situ, providing a method for quickly analyzing the presence of cells in test samples and their energy status.…”
Section: Introductionmentioning
confidence: 99%
“…Cell viability evaluation by the ATP assay is the fastest, most sensitive and least prone to artefacts than other method. Additionally, the luminescent signal stabilizes 10 min after the addition of the reagent and becomes half quenched after 5 h [54]. Variations into ATP assay sensitivity are much more due to pipetting errors than a result of the chemistry behind the assay.…”
Section: Atp Assaymentioning
confidence: 99%